Spatiotemporal analysis and environmental risk factors of visceral leishmaniasis in an urban setting in SAo Paulo State, Brazil - Prestes-Carneiro, Luiz E.; Daniel, Loris A. F.; Almeida, Livia C.; D'Andrea, Lourdes Zampieri [UNESP]; Vieira, Andre G.; Anjolete, Ivete R.; Andre, Lenira [UNESP]; Flores, Edilson F. [UNESP] (Bmc, 2019)
BackgroundIn Latin America, Brazil harbors the most cases of human visceral leishmaniasis (HVL). Since the early 1980s, the disease has spread to the urban centers of the north, and now the south and west of Brazil; it reached SAo Paulo state in the southeast in 1996, and Presidente Prudente in the western region in 2010. Our aim was to describe the spatiotemporal analysis and environmental risk factors associated with the dispersion of VL in Presidente Prudente, an urban setting with recent transmission.MethodsAn entomological survey was carried out from 2009 to 2015. A canine visceral leishmaniasis (CVL) serosurvey was performed from 2010 to 2015 using enzyme-linked immunosorbent assays (ELISA), a dual-path platform CVL rapid test, and indirect fluorescent antibodies (IFAT). Data from HVL cases were obtained from the Municipal Surveillance Epidemiology Center from 2013 to 2017. Data on water drainage and forest fragments were obtained from public platforms and irregular solid-waste deposits were determined by monthly inspections of the urban area. Kernel density maps of the distribution of CVL were constructed.ResultsFrom 2009 to 2015, Lutzomyia longipalpis sand flies were found in all seven areas of Presidente Prudente. From 2010 to 2015, 40,309 dogs were serologically screened and 638 showed positive results, i.e. a prevalence rate of 1.6%. From 2013 to 2017, six human cases were diagnosed with a mortality rate of 33.3%. In 2015, 56 points of irregular solid-waste deposits were identified, predominantly in the neighborhoods. Three different hotspots of CVL showed an increased distribution of vectors, seropositive dogs, irregular solid-waste deposits, forest fragments and water drainage.ConclusionsThe use of tools that analyze the spatial distribution of vectors, canine and human VL as environmental risk factors were essential to identifying the areas most vulnerable to the spread or maintenance of VL. The results may help public health authorities in planning prevention and control measures to avoid expansion and future outbreaks.
Keywords: Lutzomyia longipalpis; Entomological survey; Canine visceral leishmaniasis; Human visceral leishmaniasis